Pengaruh Substitusi Kolagen Tulang Ikan Lele (Clarias Sp) Pada Sabun Padat Transparan Terhadap Hasil Uji Organoleptik - Amalia, Tiara Dewi; Ainiyah, Roisatula (Lempuk: Jurnal Ilmu Kelautan dan Perikanan, 2022)
Catfish (Clarias sp) is one type of fish that lives in fresh water and is widely cultivated because it has economic value. Several processing industries derived from catfish produce waste in the form of bones, heads, entrails, scales, and skin. Fishery waste can be used as a product, one of which is collagen. Collagen can be derived from the bones of freshwater fish such as catfish (clarias sp). Collagen is a fibrous protein that gives strength and flexibility to tissues and bones and plays an important role in other tissues including skin and tendons. Currently, care products containing collagen are in great demand by the public. Soap is a cleanser with water media. Soap is made in two ways, namely the saponification process and the oil neutralization process. This study aims to determine the effect of bone collagen substitution of catfish (Clarias sp.) on moisture content, pH, and foam stability and the effect of substitution of bone collagen of catfish (Clarias sp.) on transparent solid soap on organoleptic test results. The method in this study used RAL with variations of 0g catfish bone collagen substitution; 2g; 4g; 6g; 8g substituted in 100g transparent solid soap. The results of the catfish bone collagen soap were tested by analysis of water content, pH, foam stability, and organoleptic tests (color, aroma, foam, rough impression, and itching reaction). The research data were analyzed using Analysis of variance (ANOVA) followed by Tukey's test and nonparametric statistics, namely Kruskal Wallis, while the organoleptic test data were analyzed using the Friedman test with a significance level of 5%. The best treatment uses the De Garmo method. The results showed that the addition of catfish bone collagen had a significant effect on water content, pH, and stability of transparent solid soap foam, and the effect of the treatment of catfish bone collagen substitution on transparent solid soap, there was a significant difference in the organoleptic results of color, aroma, foam and a rough impression but there was no significantly different to the organoleptic results of itching reactions. The best treatment for adding catfish bone collagen to transparent solid soap was obtained in treatment P2 (4 grams of Catfish Bone Collagen) with organoleptic test parameters including color 7.20 (like), aroma 6.80 (like), foam 8.12 (very good). like), bad impression 7.00 (like), itching reaction 7.00 (like).